EVALUASI PENGGUNAAN ANTIBIOTIKA DAN ANALISIS BIAYA PADA PASIEN RAWAT INAP BEDAH ORTHOPEDHI DI RSUD MOEWARDI SURAKARTA TAHUN 2013 - , Carolina Eka Waty, Dr. Tri Murti Andayani, Sp. FRS., Apt. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
In orthopedic surgery required the use of antibiotics to prevent infection after surgery. The rationality of the use of antibiotic therapy should achieve success in order, to avoid further infection. This study aims to describe the use of antibiotics, rational antibiotic use, cost analysis and determine the factors that affect the total cost of patient care in hospitals orthopedic surgeon at Dr. Moewardi Surakarta in 2013. This study is cross-sectional and retrospective data collection. His subjects were patients who had undergone orthopedic surgery during the period of January to December 2013 in the Hospital Moewardi Surakarta. Data retrieved from the medical records, finance and pharmaceuticals in hospitals Moewardi Surakarta. Analysis of rationality includes the right indication, the right drug, right patient, right dose and route of administration. To determine the factors that affect the total cost used one way ANOVA and independent sample t test. The results of this study, 99 subjects of research. Older patient care the most are <6 days (50.5%). The rationality of the use of antibiotics in orthopedic surgery patients include: precise indication of 100%, the selection of appropriate preoperative medication exactly 53.53% and 60% postoperative medication, right patient 100%, most are old antibiotics for 3 days 17,17%. Class of antibiotics most widely used is the cephalosporin class 1. Total cost of care is divided into three : medical costs Rp. 4.16187 million, medical support Rp 6,657,296 and non-medical Rp. 456 369. Patient characteristics that affect the total cost of care that nursing class p = 0.00, long hospitalization and p= 0.012, p= 0.003 kinds of services.